THE NAMES OF ASAHAN AS PRAYER MEDIA IN THE NELONI TRADITIONAL CEREMONY IN PONOROGO REGENCY (ETHNOLINGUISTIC STUDY) - Ahmad Riza Fauzi; Wakit Abdullah Rais; Prasetyo Adi Wisnu Wibowo (Universitas Sebelas Maret, 2023)
The Javanese are the largest ethnic group in Indonesia. Javanese society has a characteristic that is fond of carrying out traditions related to life, such as the life cycle tradition, namely the neloni tradition. The people in Ponorogo Regency are Javanese people who have lived through a long period and various problems related to their lives so that a cultural system is formed in their identity. The neloni tradition according to the Ponorogo community is a tradition to ask for safety and blessings when a pregnant woman is about three months old. In the neloni tradition, there are offerings or sharpening devices. Sharpening has various forms and names. The focus of this research examines the meaning of